Implementasi Sistem Penerimaan Mahasiswa Baru Universitas Bina Insani - Putro Dwi Mulyo; Mardi Yudhi Putra (LPPM UBHINUS MALANG, 2025)
New student admission is a very important process in higher education that requires fast, accurate, and organized information. At Bina Insani University, this process was previously done manually and using WhatsApp messaging services directly by the admin, which caused delays in response, repeated questions, and difficulties in managing registration documents. The purpose of this research is to build a new student admission information system that can speed up the registration process, reduce admin workload, and centralize registration documents digitally. This research uses the Extreme Programming (XP) method with data collection techniques through observation, interviews, and literature studies. This system is implemented using CodeIgniter with MySQL database and integrates real-time notifications via WhatsApp and Email using RabbitMQ architecture as a message broker. The results of the system implementation show that automatic notifications can improve the efficiency of information services, reduce repetitive questions, and speed up the response and document distribution process. The system also facilitates the search for registration documents with Google Drive integration. In conclusion, this system makes a significant contribution in improving the quality of new student admission services at Bina Insani University.